Confinement-Induced Fabrication of Liquid Crystalline Polymeric Fibers - Jae Gwang Kim; Jae Gyeong Lee; Jeong Jae Wie (Molecules, 2022)
In aqueous media, liquid crystalline droplets typically form spherical shapes in order to minimize surface energy. Recently, non-spherical geometry has been reported using molecular self-assembly of surfactant-stabilized liquid crystalline oligomers, resulting in branched and randomly oriented filamentous networks. In this study, we report a polymerization of liquid crystalline polymeric fibers within a micro-mold. When liquid crystal oligomers are polymerized in freely suspended aqueous media, curvilinear and randomly networked filaments are obtained. When reactive liquid crystalline monomers are oligomerized in a micro-channel, however, highly aligned linear fibers are polymerized. Within a top-down microfabricated mold, a bottom-up molecular assembly was successfully achieved in a controlled manner by micro-confinement, suggesting a unique opportunity for the programming architecture of materials via a hybrid approach.